Targeting Oncogenic Drivers and Signaling Pathways in Hematologic Malignancies From Concept to Practice [Internet] - O'Conner, Owen A.; Ansell, Stephen; Seymour, John F. (Wiley-Blackwell, 2023)
oncogenic drivers; signaling; pathways; hematologic malignancies; cancer